(untitled) - Budd, John (Chicago, 2005)
The Changing Academic Library is a revision of Budd's The Academic Library: Its Context, Its Purpose, and Its Operation. This book has been completely updated and revised to reflect the dynamic states of higher education and academic libraries. It presents a critical examination of major issues facing colleges and universities and the unique challenges that their libraries must come to grips with. Current practice is reviewed, but it is examined in the broader context of educational needs, scholarly communication, politics and economics, technology, and the nature of complex organizations
Keywords: Academic libraries,Thư viện đại học; United States,Hoa Kỳ